2014
DOI: 10.3399/bjgp14x679723
|View full text |Cite
|
Sign up to set email alerts
|

Patient-initiated camera phone images in general practice: a qualitative study of illustrated narratives

Abstract: BackgroundCamera phones have become ubiquitous in the digital age. Patients are beginning to bring images recorded on their mobile phones to share with their GP during medical consultations. AimTo explore GP perceptions about the effect of patient-initiated camera phone images on the consultation. Design and settingAn interview study of GPs based in rural and urban locations in Australia. MethodsSemi-structured telephone interviews with nine GPs about their experiences with patientinitiated camera phone images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 13 publications
(22 reference statements)
7
26
0
Order By: Relevance
“…Tan, et al (2014) found the same results with another small study population, suggesting that somewhere between 10-25% of providers will not use patient generated health data in clinical care. Inhibitors for clinicians to accept data include risk management, legal implications, duplication of data, retention, policy development (Archer et al, 2013) data security (Casper & McDaniel, 2015;Huba & Zhang, 2012) interoperability (Leventhal, Cummins, Schwartz, Martin, & Tierney, 2015;Sujansky & Kunz, 2015;Taylor, 2013) and data tagging (Leventhal, et al, 2015;Van Doornik, 2013).…”
Section: Patient and Provider Heterogeneitysupporting
confidence: 70%
See 4 more Smart Citations
“…Tan, et al (2014) found the same results with another small study population, suggesting that somewhere between 10-25% of providers will not use patient generated health data in clinical care. Inhibitors for clinicians to accept data include risk management, legal implications, duplication of data, retention, policy development (Archer et al, 2013) data security (Casper & McDaniel, 2015;Huba & Zhang, 2012) interoperability (Leventhal, Cummins, Schwartz, Martin, & Tierney, 2015;Sujansky & Kunz, 2015;Taylor, 2013) and data tagging (Leventhal, et al, 2015;Van Doornik, 2013).…”
Section: Patient and Provider Heterogeneitysupporting
confidence: 70%
“…As the research is nascent (Chung & Basch, 2015) expert opinion on the projected use of PGHD and actual empirical findings have been distinguished. Tang et al 2006;Ahern et al 2011;Huba & Zhang, 2012;Archer et al 2013;Allen et al 2016;Chung & Basch 2015;Fountain 2014 (Reduced); Tan et al 2014. Table 2.…”
Section: Patient Generated Health Datamentioning
confidence: 99%
See 3 more Smart Citations